Lean Manufacturing e Lean Accounting Cost: um enfoque no real desempenho em empresas de capital aberto na BOVESPA - Teixeira, Hipólito Francisco (2016)
This study and reaserch have targeted a field much explored nowadays, Lean Accounting through of the companies that implemented the filosofy of the Lean manufacturing.The Companies inside this dynamic enviroment, no predictible and competitive had looking for adopting strategies targeting their own survival and being diferent.In this way, new production Technologies and accounting control have been necessary.Lean accounting can be understood as a set of management accounting tools adapted and structured with models of specific decision to supply the decision process where They are adopting or adopted the values and the principles of the Lean Production.Considering these concepts we can definy the following question for this reasearch:With the implementations of this process of the production and the Lean accounting Cost, have the Brazilian companies obtained a good result in decreasing the level of available inventories? Did the Brazilian Companies really could delivery order from exclusively order from the clients, order – production – delivery? Did the Gross margins of the products and net income reflect te high financial investments in trainning that justified the spent time in this changing culture of work? Other question from this work to be considered is if the companies had improved and set their internal accounting system for given right support in this Lean Manufacturing. We should recognize the existence of a new Field of knowledge rising from renewed enterprising practices in managment accounting. In this direction those new practices need of future development and new evidences for the future, as well new systems e collecting of new results